Human-Data Interaction Syllabus for Undergraduate and Graduate Courses - Coleti, Thiago A. (2024)
The phenomenon of the data deluge is a reality and the volume of data produced by people and companies is much greater than what can be handled and analyzed. Data play a crucial role in guiding the efficient utilization of technological resources for companies, aiding them in product and service management. Moreover, individuals who have become adept data producers and consumers are increasingly orienting their lives toward data. To address this evolving trend, there is a growing imperative to educate Computing professionals. These professionals are required to design technology solutions that facilitate the synergy between individuals and data, a phenomenon known as Human-Data Interaction (HDI). This paper introduces a suggested minimum syllabus for HDI courses, with the aim of addressing the key themes associated with the interaction between individuals and data. The complexity and depth of HDI topics justify a dedicated course, preventing the risk of essential content being fragmented or inadequately covered if dispersed across different courses.